Fetal and Maternal Risk Factors Associated With Birth Trauma - A.Alghafoor, Intisr; Saadoon.Hasan, Ghusoon (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Back ground Birth traumas contribute significantly to the perinatal morbidity and mortality, sometimes with long term squeals in developing countries.Objective: To identify  the  main risk factors associated with birth trauma.Setting: Maternity Teaching  Hospital/Baby Care Unit /mosul.Design: Case-control study.Patients: There were 136 cases and 136 controls.Measures: The following variables  were recorded : a) maternal variable: age  and parity , deliveryvariables: spontaneous vaginal deliveries ,assissted instrumental vacuum or forceps delivries, deliveries by cesarean section ; b) newborn variable : type of injury ,site of injury  ,birth weight, gestational age, fetal presentation .Results: Mode of delivery , primiparous , maternal age 3.5kg were  found to be highly associated with birth trauma.   Conclusion: Risk factors associated with birth injuries identified in this study involved maternal conditions , neonatal conditions and mechanism of delivery.